STUDENT BUSINESS INCUBATOR ASA CENTER FOR YOUTH INNOVATIVE ENTREPRENEURSHIP AT THE CONTEMPORARY UNIVERSITY - Olga R. Chepyuk; Maria Yu. Ginzburg (Высшее образование в России, 2016)
This article describes the formats of interaction between Student Business Incubator as a center for youth innovative entrepreneurship at the contemporary university and departments and external environment of theuniversity. The authors analyze the problems and suggest solutions based on the experience of the activities of Student Business Incubator of the Lobachevsky State University of Nizhny Novgorod, which is the center for youth innovative entrepreneurship in the region.